Study on the shelter and sand control effect of new porous sand barriers from recycled wind turbine blades - He, Chenchen; Liu, Benli; Yin, Daiying; Li, Minlan; Hu, Caizhi; Xiao, Xiang; Duan, Yan; Fang, Minghao; Hou, Pengtao (International Soil and Water Conservation Research, 2025)
Aeolian disasters pose considerable threats to socioeconomic systems, ecological environments, and infrastructures such as railways and highways, in arid and semiarid regions. To reduce these problems, mechanical sand control measures are needed, with sand barriers being the most widely applied. However, conventional materials of sand barriers, such as crop straws, reeds, branches, High-Density Polyethylene (HDPE), and biodegradable Polylactic Acid (PLA), have drawbacks, including susceptibility to aging, unsuitability for extreme temperatures and severe wind erosion, as well as short service life. This study introduces new porous sand barriers made from decommissioned or damaged wind turbine blades. The results of mechanical performance testing, wind tunnel experiments, and numerical simulations indicated that the bending strength of the new sand barrier was 14 times that of wood composite materials and its erosion rate can be 56% lower. The new sand barriers with different porosities effectively reduced sediment transport, and the optimal porosity was found to be 20%; while higher or lower porosities were detrimental to sand control. The combined advantages of porous structure, flexibility, and strength of this new sand barrier make it well suited for regions with strong winds, large temperature variations, and intense ultraviolet (UV) radiation. Utilizing decommissioned or damaged wind turbine blades as sand control materials shows great potential for application.